An Analysis Minimal Exchange Structures and General Exchange Structure in English Classroom Interaction Found in Youtube - Regina Marintan Silalahi (IJET (Indonesian Journal of English Teaching), 2021)
Abstract. This research reported study about analysis minimal exchange structures and general exchange structure in English classroom interaction found in you tube, (from mujikuy channel : asking and giving information about berbasis ganre in x class). This study direct to analysis the element of minimal exchange structures and general exchanges structures in English classroom interaction find in you tube. The data is the clauses obtained from conversation among teacher and students of X grade during English classroom learning process that find in you tube from (Mujikuy channel : asking and giving information about berbasis ganre in x class). This study uses theory of Halliday (1994) by qualitative descriptive method. The result shows that there are three (3) types of act as the element of exchange structures: Initiating, Responding,and Following-Up (I-R-F). Minimal exchange structure consists of: Initiating-Responding (I-R) or Initiating-Responding-Following Up (I-R-F). General structure of exchange in classroom situation consists of: greeting, giving order, giving information, asking question, and closing. In the learning process, things do not always go well. When the learning process students sometimes do not respond to conversations or instructions given by the teacher. Therefore teachers must take initiatives such as providing information, asking questions, and giving instructions. So that the learning process becomes more efficient. This study shows that the teacher has the authority to regulate learning activities